Analysis of United Nations Attitudes in Upholding Human Rights: Taliban's Violent Action Against Afghan Population - Jennifer Sakti Ramadhani; Meiliani Nur Azizah; Khairul Munzilin (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
Taliban is a conventional political group and a religious faction that adheres to Sunni Islam in Afghanistan. In 1998 Taliban group began to control the Afghan region of Kabul to this day. During the leadership of the Taliban, many regimes, policies, and prohibitions for the people of Afghanistan violated human rights. Given this case, this study aims to analyse how the role of the United Nations as an international organization deals with conflict and upholds human rights in Afghanistan. The research method used is a qualitative approach by reviewing previous studies based on the concepts of human rights and justice in Islam that are relevant to the case. The United Nations played an important role in mitigating this conflict through the establishment of a special committee by the United Nations called UNAMA (United Nations Assistance Missions in Afghanistan) and sending special forces to monitor the people of Afghanistan and report on the progress of actions by the Taliban. The United Nations Security Council has made resolution No. 2513 of 2020 which contains the Joint Declaration between the governments of the United States and Afghanistan. The United Nations has been instrumental in addressing this ongoing Taliban conflict in various ways and strategies deployed to the Afghan community in protecting and enforcing human rights.